ANALISIS PENGARUH ECONOMIC VALUE ADDED TERHADAP MARKET VALUE ADDED PADA 20 EMITEN TERAKTIF DI BURSA EFEK JAKARTA PERIODE 2001 2005 - Wibowo Wibowo; Koes A Windyarti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
Generally, the purposes of company are for increasing the profit and creating shareholders wealth. Economic Value Added is a system which suitable to measure economic profitability of the company, that state the wealthy only can create if the company can fulfill all of the operating cost and cost of capital. The objectives of composing this thesis to get the empirical illustration about Economic Value Added (EVA), Market Value Added (MVA), and to know the impact Economic Value Added toward Market Value Added on 20 companies listed in Jakarta Stock Exchange (JSX) which perform the most active stock period 2001 until 2005. These data researches get from secondary data with purposive random sampling method, such as Jakarta Stock Exchange (JSX) Statistics and Indonesian Capital Market Directory (ICMD). In this thesis, the research design used is correlation descriptive method which EVA treated as independent variable and MVA as dependent variable. The conclusion is that EVA has increased every year as MVA during 2001-2003, but in 2004- 2005 the MVA has decreased, and moreover. EVA was positively influencing MVA but least significant on 20 companies that have most active stock listed in Jakarta Stock Exchange (JSX).